Presence of anticholinergic pesticide (organophosphate and carbamate) in fruits and vegetable in Cabo Frio city, RJ - Oliveira, Claudia Cristina Machado de Figueiredo de (2010)
The study used acetylcholinesterase enzyme inhibition to detect organophosphate and carbamate pesticides in fruits and vegetable consumed in the City of Cabo Frio. Vegetable and fruits collected in the area in distinct years (1996 and 2007) present pesticide in all samples. The samples of lettuce (1996) and watercress (2007) presented the highest rates of parathion-metyl equivalent 0,7 and 1,4 ppm, respectively. The lowest levels were detected in grapes: 0,2 ppm. The solubilization of compounds involved in the study in Triton X-100 were efficient without inhibiting the activity of acetylcholinesterase enzyme. Among the samples studied, lettuce, watercress and apples are valuable in the monitoring of residues of organophosphorus and carbamate pesticides.